Improvement of a commercial calcium phosphate bone cement by means of drug delivery and increased injectability. Issue 22 (15th November 2022) - Ribeiro, N.; Reis, M.; Figueiredo, L.; Pimenta, A.; Santos, L.F.; Branco, A.C.; Alves de Matos, A.P.; Salema-Oom, M.; Almeida, A.; Pereira, M.F.C.; Colaço, R.; Serro, A.P.
Abstract: Calcium phosphate cements (CPCs) have been increasingly used as synthetic bone substitutes for repair and regeneration of bone defects given their biocompatibility, resemblance to bone and malleability. Moreover, their use as local antibiotic delivery systems is of main interest against bone infections, avoiding the adverse effects of high dosages of conventional therapy. The main goals of this work were to improve the properties of a commercial CPC (Neocement®), turning it injectable, and to provide it with a new functionality as a drug delivery system able to ensure a sustained release of an antibiotic commonly used in orthopaedics (gentamicin sulphate, GS). For this, the influence of the liquid phase amount (%LP) and type of polymer contained in the formulation (chitosan, Chi, or hydroxypropyl methylcellulose, HPMC) on the basic properties of the material was evaluated. It was found that the formulation containing 42%LP + HPMC+1.87% wt GS was the best one. It showed suitable setting and mechanical properties, and injectability around 87% (much superior to the original Neocement®, with 31%). It ensured a sustained release of GS for at least 14 days, at antibacterial levels. The antibiotic released is highly effective against S. epidermidis, but also presents some antibacterial activity against S. aureus . The CPC revealed to be non-cytotoxic. Moreover, it demonstrated good flowability and connectivity with human cadaveric trabecular bone.